PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 67 PEMATANG PUDUKECAMATAN MANDAU TAHUN AJARAN 2015/2016 - Herlina Perlanti Dewi; Hendri Marhadi; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the low yield learning science students, this can be seen from the results of the fourth grade students learn the science of SD Negeri 67 Pematang Pudu, with the average value of the class 64.61. Therefore, the researchers provide learning alternatives to the application of Quantum Teaching in Elementary School fourth grade 67 Pematang Pudu. This study aims to improve learning outcomes IPA fourth grade students of SD Negeri 67 Pematang Pudu to Implementation Model Quantum Teaching. Design research is action research (PTK) with two cycles. Subjects were students in the fourth grade Pematang Pudu 67 countries consisting of 16 male students and 10 female students with heterogeneous capabilities. The research data consists of the data is a learning process and student learning outcomes data. Data instrument consists of tools and instruments to learn to collect data. Based on the analysis of research data after applying the model of Quantum Teaching, the average percentage of teachers in the first cycle of activity increased 64.58% to 83.33% in the second cycle. The average percentage of student activity also increased, which is 58.33% in the first cycle increased to 79.16% in the second cycle. learning outcomes in basic score with the average value of 64.61 and the first cycle of students increased by an average value of 72.69 with an increasing percentage of classroom learning achievement of 11.11% and the percentage of students who completed 65.38%, and the second cycle increased again to an average of 75.19 with the percentage improvement class learning outcomes 14.07% and the percentage of students who completed 80.76%. These results suggest that application of the model Quantum Teaching can improve learning outcomes IPA fourth grade students of SD Negeri 67 Pematang Pudu.Key Words: Quantum Teaching, learning outcomes IPA